The Effect of Skill Level Matching in Cooperative Dyadic Interaction on Learning of Forehand Table Tennis Skills in Adolescent Girls - Elahe Siavashi; Ali Heyrani; Ehsan Zareian (University of Tehran, 2021)
The aim of this study was to investigate The effect of skill level matching in cooperative dyadic interaction on learning of forehand table tennis skills in adolescent girls. Participants were selected convenience sampling form from 24 junior high school girls in Nahavand city and were randomly divided into two groups of Novice-Novice and Novice-Expert. Both groups performed five sessions of participatory dyad training with their respective arrangement (novice- novice, novice- expert) that each session consisted of 20 sets of 3-minute with a 1-minute rest time between sets. Using table tennis forehand shot accuracy test, the motor performance was measured in the pre-test, post-test, retention and transfer stages (Merely forehand performance with increasing throwing speed of ball thrower). The results showed that both Novice-Novice and Novice-Expert groups showed significant progress learning of forehand table tennis skills; Also, the Novice-Expert performed better in the post-test, retention and transfer stages than the Novice-Novice group. Therefore, Novice-Expert arrangement than Novice-Novice during participatory dyad training facilitates learning forehand table tennis skill.It revealed that novice-expert arrangement is more efficient in comparison to novice-novice arrangement as the former enjoys the benefits of using the optimal observational pattern (seeing a expert person), and offeres various challenges and strategies for the novice partner as a result of exercising with an expert partner. To conclude, novice-expert dyad practice promotes the speed of learning among table tennis learners.